A NEW BASAL NEOPTERYGIAN FROM THE MIDDLE TRIASSIC OF LUOPING COUNTY (SOUTH CHINA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
A new taxon belonging to Neopterygians is described, based on very nicely preserved specimens from the rich vertebrate levels recently discovered in Luoping County, Yunnan Province, South China. This new assemblage dates to Pelsonian (Anisian, Middle Triassic), about the same age of the Panxian Fauna from the nearby Guizhou Province. The Luoping Fauna, yielding this new taxon, is turning out to be one of the most important fish faunas of the whole Middle Triassic and the oldest evidence of the fish radiation of this time span. This new genus of basal neopterygian shows unique derived characters, especially for the almost naked body, with a single row of urodermals covering the body lobe in the tail and a row of very small and thin scales bearing the lateral line canal along the flank. Also in the axial skeleton the new taxon shows peculiar characters such as the neural spines perfectly aligned to each paired neural arches and abdominal ribs well developed. Concerning skull bones, no suborbitals have been detected.
Keywords: New taxon; Basal Neopterygians; Middle Triassic; Tethys; South China